(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Yersinia pestis (Y. pestis) is a gram-negative bacteriam.it cause plague disease. Between 30% and 100% of untreated patients die, with pneumonic plague being the deadliest. Chloramphenicol Streptomycin and tetracycline are the three main antibiotics that are used for plague treatment. Even if antibiotics are given right away, 16% of people with bubonic plague and more than 50% of people with pneumonic plague die. The number of plague cases and epidemics over the past 15 years has increased to the point where the disease is now considered reemerging. Researchers have discovered that some strains of the plague are immune to the most effective medications now in use to treat the disease. Y. pestis is worrisome since there is no effective vaccination, it must be treated with antibiotics, and it has a history of being used as a bioweapon. Antibiotic-resistant bacteria are a worldwide problem. It has been revealed that two strains of Y. pestis are highly resistant to eight antimicrobial medicines used for cure. Additionally, it is resistant to a number of commonly used antibiotics, including ampicillin, kanamycin, and spectinomycin. In subtractive genomics approach the bacterial total proteome is gently nethermost to a few numbers of probable targets for drug. The steps which are applied in this method to detect targets proteins which are non-similar to human and are vital for bacteria and contribution of the sorted out proteins in bacterial pathways of metabolism that are vital for continuity of pathogen. In this study the approach of subtractive genomics is applied on proteins of Y. pestis and culminated with 4 proteins that may be powerful drug targets and novel zestful molecules can be designed against them to cure the bacteria associated infection.